Sleep-Stage-Specific Regulation of Cortical Excitation and Inhibition - Niethard, Niels; Hasegawa, Masashi; Itokazu, Takahide; Oyanedel, Carlos N.; Born, Jan; Sato, Takashi R. (Current biology, 2016)
Sleep is characterized by unique patterns of cortical activity alternating between the stages of slow-wave sleep (SWS) and rapid-eye movement (REM) sleep. How these patterns relate to the balanced activity of excitatory pyramidal cells and inhibitory interneurons in cortical circuits is unknown. We investigated cortical network activity during wakefulness, SWS, and REM sleep globally and locally using in vivo calcium imaging in mice. Wide-field imaging revealed a reduction in pyramidal cell activity during SWS compared with wakefulness and, unexpectedly, a further profound reduction in activity during REM sleep. Two-photon imaging on local circuits showed that this suppression of activity during REM sleep was accompanied by activation of parvalbumin (PV)+ interneurons, but not of somatostatin (SOM)+ interneurons. PV+ interneurons most active during wakefulness were also most active during REM sleep. Our results reveal a sleep-stage-specific regulation of the cortical excitation/inhibition balance, with PV+ interneurons conveying maximum inhibition during REM sleep, which might help shape memories in these networks. •Cortical activity is suppressed globally during sleep, being lowest during REM sleep•During REM sleep, a subset of PV+ interneurons increase their activity•Neurons that are active during wake tend to show higher activity during REM sleep Niethard et al. show that REM sleep is associated with a global suppression of cortical neural activity, which is accompanied by a specific activation of parvalbumin-positive inhibitory interneurons.